EFEKTIVITAS MIKROORGANISME ANTAGONIS TERHADAP PENYAKIT KARAT PUTIH PADA TANAMAN KRISAN (Chrysanthemum morifolium Ramat) DI KOTA TOMOHON - Aprilia N. Rares; Emmy Senewe; Guntur S.J. Manengkey; Max M. Ratulangi (COCOS, 2015)
ABSTRACT Chrysanthemum or Chrysanthemum marifolium Ramat is one of the types of cut flowers have bright market prospects. As one of the types of ornamental plants, dubbed "King of Cut Flowers" besides having a shape and color which is very interesting, this plant has already started a lot of fans. Diseases that attack chrysanthemum eg rust disease caused by the fungus Puccinia sp. Damage results because this rust disease attacks especially on susceptible plants can reach 100% or crop failure. Rust diseases Puccinia sp. This allegedly carried on planting material (seeds) that has spread to many locations planting chrysanthemums. Tomohon is a center for the production of ornamental plants, especially chrysanthemum in North Sulawesi. Preliminary observations in planting chrysanthemums in Tomohon showed white rust disease. The purpose of this study was to look at and examine the effectiveness of microorganisms antagonistic Trichoderma sp., Pseudomonas fluorescens and Paenibacillus polymyxa to disease chrysanthemum white rust on research was conducted by using the method of randomized block design with four treatments namely A control treatment without application of antagonistic microorganisms, treatment B the application of microorganisms antagonistic Trichoderma sp., the treatment C with application of microorganisms antagonistic P. fluorescens and treatment D with application of microorganisms P. polymyxa. This treatment was repeated 5 times. Rating affected leaves using index calculation disease (severity). The variables measured are severity of affected leaves, leaf number and plant height. The results showed that of some microorganisms are used, equally effective in controlling the disease chrysanthemum white rust is antagonistic microorganism Trichoderma sp. with the value of the average severity of the last observation was 17.71%, followed by P. polymyxa with the average value of 26.78% last severity. Furthermore, the third treatment antagonistic microorganisms do not give effect to the number of leaves and plant height. Â Keyword: Chrysanthemum, P. horiana, Trichoderma sp., P. fluorescens, P. polymyxa